Food‐induced anaphylaxis morbidity: Emergency department and hospitalization data support preventive strategies. Issue 8 (21st July 2021) - Tanno, Luciana Kase; Clark, Evangeline; Mamodaly, Myriam; Cardona, Victoria; Ebisawa, Motohiro; Asontegui, Ignacio; Sanchez‐Borges, Mario; Santos, Alexandra F.; Fiocchi, Alessandro; Worm, Margitta; Caimmi, Davide; Latour Staffeld, Patricia; et al.
Abstract: Background: Anaphylaxis is a recognized public health issue. There is no doubt that food‐induced anaphylaxis (FIA) has tremendous impact on the quality of life of patients and their families and increases direct and indirect costs. FIA is associated with increasing rates of emergency department admissions and hospitalizations and implies the risk of death. Morbidity epidemiological data are a key to tailor public health actions to this non‐communicable disease. The aim of this article was to review published morbidity epidemiological data relating to FIA and potential risk factors, in order to provide evidence‐based recommendations to reduce the risk of severe adverse outcomes. Methods: We identified published studies available in PUBMED/MEDLINE (1966–2020), EMBASE (1980–2020) and CINAHL (1982–2020). The systematic review was carried out using MeSH terms related to FIA ED admissions and hospitalizations. Results: A total of 25 articles were selected, 80% published in the last 5 years. After critical analysis of methodological and clinical characteristics reported in the data selected, we were able to propose preventive strategies. Conclusion: Anaphylaxis is a recognized public health issue. FIA is associated with increasing rates of ED admissions and hospitalizations and imply in risk of death. More than reviewing and critically interpreting the key patterns related to FIA morbidity published data, we proposed strategies in order to promote quality care of patients suffering from FIA. Our World Health Organization Collaborative Center is deeply involved in this process, and we believe that the proposed strategies will inform future healthcare policies on anaphylaxis. The long‐term objective would be to improve clinical care and quality of life of patients and their families, and develop risk‐stratified, cost‐effective preventive measures.